Randomized Controlled Trial of Radiation Protection With a Patient Lead Shield and a Novel, Nonlead Surgical Cap for Operators Performing Coronary Angiography or Intervention. (August 2015) - Alazzoni, Ashraf; Gordon, Chris L.; Syed, Jaffer; Natarajan, Madhu K.; Rokoss, Michael; Schwalm, Jon-David; Mehta, Shamir R.; Sheth, Tej; Valettas, Nicholas; Velianou, James; Pandie, Shaheen; Al Khdair, Darar; et al.
<x xml:space="preserve">Abstract</x> Background— Interventional cardiologists receive one of the highest levels of annual occupational radiation exposure. Further measures to protect healthcare workers are needed. Methods and Results— We evaluated the efficacy of a pelvic lead shield and a novel surgical cap in reducing operators' radiation exposure. Patients undergoing coronary angiography or percutaneous coronary intervention (n=230) were randomized to have their procedure with or without a lead shield (Ultraray Medical, Oakville, Canada) placed over the patient. During all procedures, operators wore the No Brainer surgical cap (Worldwide Innovations and Technology, Kansas City, KS) designed to protect the head from radiation exposure. The coprimary outcomes for the lead shield comparison were (1) operator dose (µSv) and (2) operator dose indexed for air kerma (µSv/mGy). For the cap comparison, the primary outcome was the difference between total radiation dose (µSv; internal and external to cap). The lead shield use resulted in a 76% reduction in operator dose (mean dose, 3.07; 95% confidence interval [CI], 2.00–4.71 µSv lead shield group versus 12.57; 95% CI, 8.14–19.40 µSv control group; P<0.001). The mean dose indexed for air kerma was reduced by 72% (0.004; 95% CI, 0.003–0.005 µSv/mGy lead shield group versus 0.015; 95% CI, 0.012–0.019 µSv/mGy control group; P<0.001). The cap use resulted in a significant reduction in operator head radiation exposure (mean left temporal difference [external–internal] radiation dose was 4.79 [95% CI, 3.30–6.68] µSv; P<0.001). Conclusions— The use of a pelvic lead shield and the cap reduced significantly the operator radiation exposure and can be easily incorporated into clinical practice. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT02128035.